2007
DOI: 10.1016/j.appet.2007.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Richter and sodium appetite: From adrenalectomy to molecular biology

Abstract: Nearly three-quarters of a century ago, Curt Richter removed the adrenal glands from rats and noted that the animal's vitality was dependent on its increased consumption of sodium chloride. In doing so, Richter revealed an innate behavioral mechanism that serves to maintain the hydromineral balance of an animal faced with sodium deficit. This experiment and others like it, led to the development of a field of research devoted to the investigation of salt appetite. The following is a discussion of how Richter's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 121 publications
2
40
0
Order By: Relevance
“…Some authors have postulated a role in salt appetite and volume regulation of local synthesis of aldosterone in the hypothalamus and circumventricular organs , but see a commentary by Funder (2005). The action exerted by aldosterone on salt appetite may occur in synergy with angiotensin II, as was observed in the salt-depleted animal model generated by furosemide administration (Sakai et al 1986, Krause & Sakai 2007.…”
Section: The Aldosterone-responsive Mr Neuronal Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have postulated a role in salt appetite and volume regulation of local synthesis of aldosterone in the hypothalamus and circumventricular organs , but see a commentary by Funder (2005). The action exerted by aldosterone on salt appetite may occur in synergy with angiotensin II, as was observed in the salt-depleted animal model generated by furosemide administration (Sakai et al 1986, Krause & Sakai 2007.…”
Section: The Aldosterone-responsive Mr Neuronal Networkmentioning
confidence: 99%
“…After adrenalectomy, salt appetite rises, which is readily normalised by aldosterone replacement, but with higher doses of the mineralocorticoid, salt appetite increases again. Glucocorticoids increase salt appetite by inducing MR and by sustaining-through activation of the mesolimbic dopaminergic level, the motivation to ingest salt (Krause & Sakai 2007).…”
Section: The Aldosterone-responsive Mr Neuronal Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of these experiments, sodium appetite was elicited prior to conditioning, rather than the reverse as in the present study. For example, Frumkin (1975) reported that adrenalectomized rats, which are in a chronic state of sodium hunger (Richter 1936(Richter , 1956Krause and Sakai 2007;Geerling and Loewy 2008), failed to form taste aversions to NaCl and concluded that sodium appetite either prevents aversive conditioning to the taste of sodium or prevents the expression of a learned aversion. In that study, however, rats had ample experience with NaCl prior to conditioning, which is known to decrease the strength of taste aversion (e.g., Kalat 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Randall R. Sakai dedicated a substantial portion of his career to understanding the hormonal signals that arise from negative sodium balance and how those signals interact with the central nervous system to drive sodium intake – a phenomenon known as sodium appetite. Randall, together with his student Eric Krause, drafted a beautiful review of sodium appetite as an homage to the revolutionary work of Curt Richter, who first described sodium appetite in 1936 [4,5]. Randall and his co-authors over the years have focused on the hormonal responses to sodium depletion and the integration of these signals by central circuits to generate compensatory physiological processes and behaviors.…”
Section: Sodium Appetite As Motivated Behaviormentioning
confidence: 99%